SOSIALISASI UPAYA PENCEGAHAN STUNTING MELALUI CINTA LINGKUNGAN DI DESA CENRANA - Nasrayanti Nurdin,; Sunandar,; Ariyana, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Stunting in Indonesia is a national public health problem that needs serious attention, because it is classified as high according to WHO standards, reaching 30-39%. Stunting reflects chronic malnutrition and can have long-term effects, resulting in stunted growth, decreased cognitive and mental abilities, susceptibility to disease, low economic productivity, and low quality of reproductive output. One of the causes of stunting can be influenced by several factors such as environmental sanitation, food processing, and also mother's knowledge of stunting. Unhealthy environmental sanitation will affect the health of children under five and in the end can affect the nutritional status of these toddlers. This activity begins with analysis, then continues with licensing and preparation of infrastructure facilities and then the implementation will be carried out on March 17, 2022 by the ITKes Muhammadiyah Sidrap community service team. This socialization was attended by 30 people from the community, 3 village officials, 2 village midwives and 10 midwifery teams from ITKes Muhammadiyah Sidrap. This socialization received support from the community with the enthusiasm of the community in participating in the activity until it was completed